Some characteristics of the Southwest Monsoon Circulation - RAO, Y. P. (MAUSAM, 1961)
The southwest monsoon is probably the largest local perturbation on the general circulation of the atmosphere, Meridional transport of mass, heat energy and angular momentum associated with the southwest monsoon circulation have been computed from the upper air data of Singapore, Nairobi, Madras, Bombay, Nagpur and New Delhi for July and August 1955. In view of the large airflow in lower levels across the equator in this period, mass exchange between the hemispheres is important. At Singapore and Nairobi, both near the equator, compensating southward flow exists at 200-and 600-mb levels respectively. There is still significant net flow northwards at Singapore and southwards at Nairobi, probably representative of the eastern and western sections of the monsoon circulation. In the southwest monsoon area due to the large cloudiness, the solar energy absorbed by the ground and the lower atmosphere decreases appreciably and is in a portion slightly less than the outgoing radiation. There is advective flux of heat from the north into this ‘sink’. Necessity and evidence for transport of heat from summer to winter hemisphere is discussed. Angular momentum flows into the monsoon area from the north and more so northwards across the equator at Singapore.